1974
DOI: 10.1530/jrf.0.0410159
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Washing on the Ultrastructure and Cytochemistry of Ram Spermatozoa

Abstract: Summary. Washing ram spermatozoa two or four times with Krebs\x=req-\ Henseleit-Ringer solution, to achieve dilution rates of 100-or 10, 000\ x=req-\ fold, damaged the plasma membranes, acrosomes and mitochondria of some spermatozoa. The proportion of spermatozoa with broken plasma membranes over the acrosome increased with the number of washes.Washing once to achieve a dilution rate of 10-fold was sufficient to remove from spermatozoa all the substrate available for NADPH diaphorase and probably glucose-6-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…We subjected the control spermatozoa to the same treatment as those exposed to pentoxifylline. In particular, our Centrifugation was pointless because centrifugation and washing are not strictly devoid of effect, especially in case of asthenozoospermia [15,19,231. The differences observed cannot be ascribed to a difference in protocol between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…We subjected the control spermatozoa to the same treatment as those exposed to pentoxifylline. In particular, our Centrifugation was pointless because centrifugation and washing are not strictly devoid of effect, especially in case of asthenozoospermia [15,19,231. The differences observed cannot be ascribed to a difference in protocol between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…By using 0.5 x lo6 r n~-I spermatozoa after swim-up in the HA medium, it was possible to keep the frequency of polyspermia lower without sacrificing the proportions of oocytes with two pronuclei. However, further reducing the number of spermatozoa to 0.25 x lo6 mL-' resulted in inconsistencies (data not shown) perhaps partly attributable to the high rate of dilution of motile cells; a high rate of dilution has been found to be detrimental to the plasma membrane, acrosome, and organelles of the spermatozoa (Jones and Holt 1974). By using fresh semen from only two bulls, the number of spermatozoa has been reduced once improved capacitation has been achieved (Guyader and Chupin 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa selected by the swim-up method are washed to remove the decapacitating coat of protein molecules incorporated from the epididymis and seminal plasma. The washing procedure, which involves repeated centrifugation, may be harmful to the spermatozoa (Jones and Holt 1974;Makler and Jakobi 1981) and may contribute, in part, to the inconsistency in the results of an IVF programme. Therefore, physical manipulation of the spermatozoa should be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in the SU technique the cen trifugation steps are often time-consuming and result in a low recovery of motile spermatozoa [10], Furthermore, centrifugation may be deleterious to the spermatozoa, and possible damage to intracellular organelles cannot be excluded [11], For some authors, semen prepared using the self-migration method containing HYA resulted in significantly more motile sperm [1, 4. 5] and a greater recovery rate of progressive motile spermatozoa [1,4] than after SU.…”
Section: Discussionmentioning
confidence: 99%